The heart that fed : a father, a son, and the long shadow of war - Sciacchitano, Carl (Gallery 13, an imprint of Simon & Schuster, LLC, 2024)
"A brilliant graphic memoir debut, this is a loving son’s exploration of his tumultuous relationship with his father, told through the lens of the Vietnam War and its lasting effects long after returning home."--Amazon.